Outcomes of early repeat sweat testing in infants with cystic fibrosis transmembrane conductance regulator‐related metabolic syndrome/CF screen‐positive, inconclusive diagnosis. Issue 12 (29th September 2021) - Terlizzi, Vito; Claut, Laura; Colombo, Carla; Tosco, Antonella; Castaldo, Alice; Fabrizzi, Benedetta; Lucarelli, Marco; Cimino, Giuseppe; Carducci, Carla; Dolce, Daniela; Biffi, Arianna; Bonomi, Paolo; et al.
Abstract: Background: Reaching early and definitive diagnosis in infants with cystic fibrosis (CF) transmembrane conductance regulator‐related metabolic syndrome (CRMS)/CF screen‐positive, inconclusive diagnosis (CFSPID) is a priority of all CF newborn screening programs. Currently, sweat testing (ST) is the gold standard for CF diagnosis or exclusion. We assessed outcomes in a cohort of Italian CRMS/CFSPID infants who underwent repeat ST in the 1st year of life. Methods: This multicentre, prospective study analysed clinical data and outcomes in CRMS/CFSPID infants born between September 1, 2018, and December 31, 2019, and followed until June 30, 2020. All subjects underwent CF transmembrane conductance regulator ( CFTR ) gene sequencing and the search for CFTR macrodeletions/macroduplications, and repeat ST in the 1st year of life. Results: Fifty subjects (median age at end of follow‐up, 16 months [range, 7–21 months]) were enrolled. Forty‐one (82%) had the first sweat chloride (SC) in the intermediate range. During follow up, 150 STs were performed (range, 1–7/infant). After a median follow‐up of 8.5 months (range, 1–16.2 months), 11 (22%) subjects were definitively diagnosed as follows: CF ( n = 2 [4%]) at 2 and 5 months, respectively; healthy carrier ( n = 8 [16%]), at a median age of 4 months (range, 2–8 months); and healthy ( n = 1 [2%]) at 2 months of age. Inconclusive diagnosis remained in 39 (78%) infants. Conclusions: Early repeat ST in the 1st year of life can shorten the time to definitive diagnosis in screening positive subjects with initial SC levels in the intermediate range.